Empirical evidence of the value of monitoring in joint ownership - Mantecon, Tomas; Liu, Ian; Gao, Fei (Journal of Banking & Finance, 2012)
Joint ownership of assets by two partners can have an adverse effect on the incentives to invest and can result in unstable and inefficient organizational structures. Control sharing, however, plays an important role in economic, political, and social institutions. There is scarce empirical evidence on the benefits of joint ownership in corporate finance. We analyze acquisitions of corporate assets by joint ventures to empirically ascertain the value of joint ownership in economic activities. The results indicate that firms experience significantly larger returns in joint acquisitions than in full-control acquisitions and that this difference is restricted to the sample of firms in which both partners share equal ownership in the target. These findings suggest that monitoring in joint ownership structures ameliorates the possibility of value-destroying corporate decisions.